Mild cognitive impairment in de novo Parkinson's disease: A neuromelanin MRI study in locus coeruleus. Issue 6 (2nd April 2019) - Li, Yuanfang; Wang, Changpeng; Wang, Jian; Zhou, Ying; Ye, Fang; Zhang, Yong; Cheng, Xiaoqin; Huang, Zhen; Liu, Kai; Fei, Guoqiang; Zhong, Chunjiu; Zeng, Mengsu; et al.
Abstract: Background: We aimed to investigate neuromelanin‐sensitive magnetic resonance imaging (NM‐MRI) features in the locus coeruleus of de novo Parkinson's disease patients with different cognitive states and to determine whether these features are associated with cognitive impairment. Methods: Three groups of subjects were recruited in this study, including patients with de novo PD with mild cognitive impairment (n = 23), patients with de novo PD without cognitive impairment (n = 48), and control subjects (n = 32). All subjects underwent clinical evaluations, as well as MRI scanning. The contrast‐to‐noise ratio of the locus coeruleus in the neuromelanin‐sensitive MRI images and cortical thickness were measured. Results: The contrast‐to‐noise ratio of the locus coeruleus in PD patients with mild cognitive impairment was significantly lower than that of controls ( P = 0.016). The contrast‐to‐noise ratio of the locus coeruleus for PD patients without cognitive impairment was intermediate between that of controls and PD patients with mild cognitive impairment. Furthermore, multiple linear regression analysis showed that the contrast‐to‐noise ratio of the locus coeruleus was negatively associated with performance on the Trail Making Test B in all PD patients, controlling for age, sex, years of education, the Unified Parkinson's Disease Rating Scale motor scores from right upper limb, Geriatric Depression Rating Scales scores, Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire scores, and cortical thickness. Conclusions: Dysfunction of the locus coeruleus neurons may partly contribute to the decline in executive function in early de novo PD. In the future, the locus coeruleus‐norepinephrine system might be targeted for early‐intervention strategies in PD patients. © 2019 International Parkinson and Movement Disorder Society